2002
DOI: 10.1074/jbc.c200330200
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the Most Common Cystic Fibrosis Mutation (ΔF508) into Human P-glycoprotein Disrupts Packing of the Transmembrane Segments

Abstract: The most common mutation in cystic fibrosis (deletion of phenylalanine 508 (⌬F508) in the cystic fibrosis conductance transmembrane regulator (CFTR) gene) causes defective synthesis of CFTR protein. To understand how this deletion interferes with protein folding, we made the equivalent deletion (⌬Y490) in P-glycoprotein (P-gp). A Cys-less P-gp with cysteines in transmembrane (TM) 4 or TM5 can be cross-linked with a cysteine in TM12. Deleting Tyr 490 in P-gp resulted in an inactive and defectively processed mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 48 publications
(42 reference statements)
3
49
0
Order By: Relevance
“…9B). Processing mutations such as G251V appear to act as thermodynamic hurdles to inhibit packing of the TM segments between TMD1 and TMD2 (6). Introduction of an arginine into position Met-68 may help to restore packing of the TM segments between TMD1 and TMD2 by forming hydrogen bonds with Tyr-950 and/or Tyr-953 in TM11.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9B). Processing mutations such as G251V appear to act as thermodynamic hurdles to inhibit packing of the TM segments between TMD1 and TMD2 (6). Introduction of an arginine into position Met-68 may help to restore packing of the TM segments between TMD1 and TMD2 by forming hydrogen bonds with Tyr-950 and/or Tyr-953 in TM11.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that introduction of arginine at positions 64, 65, 68, and 71 promotes folding of P-gp by affecting the orientation of TM1in the lipid bilayer. We previously showed that packing of the TM segments between the two TMDs is a rate-limiting state in maturation of ABC transporters such as P-gp and CFTR (6,46). Processing mutations such as G251V may alter the orientation of one or more TM segments in the membrane to interfere with subsequent packing of the TM segments at the interface between TMD1 and TMD2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of misprocessed P-gp mutants in the presence of a drug substrate, however, promotes maturation of the protein so that the protein is trafficked to the cell surface in an active form (21). Drug substrates appear to rescue misprocessed mutants by promoting domain-domain interactions (22,23).…”
mentioning
confidence: 99%